2003
DOI: 10.1074/jbc.m211617200
|View full text |Cite
|
Sign up to set email alerts
|

Glycolysis and Glutamate Accumulation into Synaptic Vesicles

Abstract: Glucose is the major source of brain energy and is essential for maintaining normal brain and neuronal function. Hypoglycemia causes impaired synaptic transmission. This occurs even before significant reduction in global cellular ATP concentration, and relationships among glycolysis, ATP supply, and synaptic transmission are not well understood. We demonstrate that the glycolytic enzymes glyceraldehyde phosphate dehydrogenase (GAPDH) and 3-phosphoglycerate kinase (3-PGK) are enriched in synaptic vesicles, form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(71 citation statements)
references
References 58 publications
2
67
0
1
Order By: Relevance
“…It has been suggested (Raffin et al, 1992;Rosenthal and Sick, 1992) that the plasma membrane Na ϩ /K ϩ -ATPase is preferentially fueled by ATP produced from glycolysis (although it is unclear why mitochondrially produced ATP cannot diffuse to plasma membrane Na ϩ pumps, and an increase in glycolytic rate via the Pasteur effect might explain why mitochondrial block has relatively little effect). Consistent with a metabolic compartmentation within cells in which glycolysis powers ion pumping, glycolytic enzymes have been detected in synaptic locations where energy use on ion pumping is high (Wu et al, 1997;Ikemoto et al, 2003). This could explain why fueling glycolysis with glucose while blocking mitochondria prevents an AD; glycolytic ATP might allow the Na ϩ /K ϩ -ATPase to function sufficiently to maintain transmembrane ion gradients.…”
Section: Metabolic Compartmentationmentioning
confidence: 58%
“…It has been suggested (Raffin et al, 1992;Rosenthal and Sick, 1992) that the plasma membrane Na ϩ /K ϩ -ATPase is preferentially fueled by ATP produced from glycolysis (although it is unclear why mitochondrially produced ATP cannot diffuse to plasma membrane Na ϩ pumps, and an increase in glycolytic rate via the Pasteur effect might explain why mitochondrial block has relatively little effect). Consistent with a metabolic compartmentation within cells in which glycolysis powers ion pumping, glycolytic enzymes have been detected in synaptic locations where energy use on ion pumping is high (Wu et al, 1997;Ikemoto et al, 2003). This could explain why fueling glycolysis with glucose while blocking mitochondria prevents an AD; glycolytic ATP might allow the Na ϩ /K ϩ -ATPase to function sufficiently to maintain transmembrane ion gradients.…”
Section: Metabolic Compartmentationmentioning
confidence: 58%
“…Thus, these studies point to a previously unrecognized role for the multifunctional CaMKII in regulating membrane ATP through targeting and activation of glycolytic enzymes such as GAPDH in response to the calcium signal. Although, PGK and GAPDH normally exist in a complex and at the SR membrane (20,39,(41)(42)(43), we were unable to detect this in our assay conditions, because this association is fragile and disrupted in 0.1 M KCl (44).…”
Section: Camentioning
confidence: 69%
“…A role for GAPDH together with 3-phosphoglycerate kinase (PGK) has been previously established in the production of ATP from GAP, NAD ϩ , P i , and ADP at the level of the SR membrane (19,20,39,40). In addition, a recent study demonstrated that synaptic vesicles were capable of generating local ATP via the membrane-associated GAPDH system, which could support the accumulation of the excitatory neurotransmitter glutamate even during significantly reduced global cellular ATP concentrations (41). It is notable that synaptic vesicles contain a CaMKII␤ isoform (42), which we found to associate with GAPDH but to a much less degree when compared with the muscle-specific isoform of the kinase.…”
Section: Camentioning
confidence: 99%
See 1 more Smart Citation
“…Four metabolic enzymes were up-regulated in the MI group suggesting an increased energy metabolism in the head of sporozoite-infected mosquitoes. A modification of metabolic enzyme activity could modify the production of ATP and consequently be detrimental to normal brain and neuronal function [34][35][36]. In the CNS of vertebrates, ATP is not only the energy source but can also act directly as a neuromodulator at purinergic synapses and as a factor with the potential to regulate: (i) neural development and plasticity; (ii) proliferation and apoptosis of glial and brain capillary endothelial cells; and (iii) the response of the nervous system to disease processes [37,38].…”
Section: Discussionmentioning
confidence: 99%